Bioindicators for Forest Area Condition: A Systematic Literature Review - Rahardjanto, Abdulkadir; Husamah, H.; Azaria, Aisha; Lubis, Citra Aulianisa; Ayuntya, Eva; Alfikri, Fauzan Wisnu (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Flora and fauna are essential components of ecosystems, playing a vital role in maintaining environmental balance. They also serve as bioindicators for assessing forest health. As a result, many researchers have focused their studies on bioindicators, as evidenced by the extensive literature published in journals. The objective of this Systematic Literature Review (SLR) is to systematically identify, study, evaluate, and interpret data from relevant journal articles. We conducted a search in the Scopus database using the keyword